Emerging roles of i-motif in gene expression and disease treatment - Luo, Xiaoqing; Zhang, Jianye; Gao, Yue; Pan, Weifei; Yang, Yayuan; Li, Xu; Chen, Lingfei; Wang, Chang; Wang, Yuqing (Frontiers in Pharmacology, 2023)
As non-canonical nucleic acid secondary structures consisting of cytosine-rich nucleic acids, i-motif structures can be formed under proper conditions. Several i-motif sequences have been identified in the human genome, and these i-motif structures play important roles in biological regulatory functions. Owning physicochemical properties, these i-motif structures draw wide attention and now become new targets for drug development. Here we recapitulated the characteristics and mechanisms of i-motifs which locating in the gene promoters (such as c-myc, Bcl-2, VEGF and telomere), summarized various small molecule ligands which interact with them and the possible binding modes between ligands and i-motifs, and described their effects on gene expression. Furthermore, we discussed the diseases closely associated with i-motifs. In particular, cancer is closely associated with i-motifs since i-motifs can form in some regions of most oncogenes. At the end of the article, we mainly introduced , as well as the recent advances of their application in multiple areas.